Resistência à insulina e risco cardiovascular: associação com o polimorfismo no gene PAI-1 e parâmetrosbioquímicos em mulheres com a síndrome dos ovários policísticos - Mariana Ferreira Sales (2012)
Polycystic Ovary Syndrome (PCOS) is the most common endocrinopathy among women, affecting 4%-8% of this group in reproductive age. This study aimed to analyze the association among metabolic, hormonal, pro-inflammatory factors and PCOS development in 63 PCOS women compared with 63 healthy women (control group). Furthermore, the frequency of 4G/5G polymorphism in plasminogen activator inhibitor 1 (PAI-1) gene was also compared between a group of 79 PCOS women and a control group with the same subject size. PCOS group presented insulin resistance, increased levels of testosterone and C Reactive Protein (CRP) and worse anthropometric and lipid profile when compared with the control group. PAI-1 levels were positively correlated with soluble vascular cell adhesion molecule-1 (sVCAM-1), lipid accumulation product (LAP), body mass index (BMI), abdominal circumference, glycemia, homeostatic model assessment - insulin resistance (HOMA-IR) e VLDL-C in PCOS group. Besides, a significant difference in allelic and genotypic frequencies in PAI-1 gene 4G/5G polymorphism was found when comparing the groups, with 4G allele showing increased frequency in PCOS group. 4G/4G genotype as associated with increased PAI-1 levels in this group, which also showed a negative correlation between vitamin D (25OHD) and sVCAM-1 levels. A positive correlation between Ferriman-Gallwey (F-G) score and BMI, abdominal circumference and insulin levels was observed in PCOS group. Therefore, sVCAM-1, 25OHD, CRP measurements and 4G allele research in PAI-1 gene might work as good predictors of the low pro-inflammatory state and cardiovascular risk observed in PCOS women. The results also point to a possible use of LAP as a tool to efficiently assess cardiovascular risk in this group. F-G score might be a better parameter than testosterone to correlate hyperandrogenism with obesity/insulin resistance. Finally, alterations in metabolic and hormonal variables evidence the pro-inflammatory and pro-atherogenic state observed in PCOS.